State-wide dissemination of a school-based nutrition education programme: a RE-AIM (Reach, Efficacy, Adoption, Implementation, Maintenance) analysis. Issue 2 (6th December 2012) - Dunton, Genevieve Fridlund; Liao, Yue; Grana, Rachel; Lagloire, Renee; Riggs, Nathaniel; Chou, Chih-Ping; Robertson, Trina
Abstract Objective The current study evaluated the overall public health impact of the 'Shaping Up My Choices' (SMC) programme, a 10-week school-based nutrition education curriculum developed for third-grade students, using the RE-AIM (Reach, Efficacy, Adoption, Implementation, Maintenance) framework. Design Randomized controlled trial to evaluate the programme and secondary analysis of archival data to describe dissemination. Data were collected from programme records, teacher surveys and student pre-, post- and 3-month follow-up surveys. Setting Public elementary schools in California. Subjects An evaluation sample (938 students and nineteen teachers) and a dissemination sample (195 245 students and 7359 teachers). Results In the evaluation sample, differences between the control and intervention groups were observed for nutrition knowledge, self-efficacy, outcome expectancies, and intakes of vegetables, fruit (girls only), soda, and low-nutrient high-energy foods from pre- to post-survey. Group differences in change in knowledge, outcome expectancies and vegetable intake were sustained through the 3-month follow-up (efficacy). One hundred per cent of intervention teachers in the evaluation sample implemented all of the lessons (implementation). The dissemination sample represented 42 % of third-grade students (reach) and 39 % of third-grade classrooms in public elementary schools in California during 2010–2011 (adoption). Thirty-seven per cent of third-grade teachers in the dissemination sample reordered SMC materials during the subsequent school year (2011–2012; maintenance). Conclusions The SMC programme demonstrates the potential for moderate to high public health impact.